Hilton's expansion into the China hotel industry - Huang, Shiling (2008)
This paper aims to analyze Hilton and its competitors in China's hotel industry, specifically in Beijing and Shanghai, through its 4Ps (Price, Place, Promotions and Products and Services). Gaps are then identified and recommendations are made to increase Hilton's market share in China.